miRNA-200c-3p targets talin-1 to regulate integrin-mediated cell adhesion - Gideon Obeng (Nature Portfolio, 2021)
Abstract The ability of integrins on the cell surface to mediate cell adhesion to the extracellular matrix ligands is regulated by intracellular signaling cascades. During this signaling process, the talin (TLN) recruited to integrin cytoplasmic tails plays the critical role of the major adaptor protein to trigger integrin activation. Thus, intracellular levels of TLN are thought to determine integrin-mediated cellular functions. However, the epigenetic regulation of TLN expression and consequent modulation of integrin activation remain to be elucidated. Bioinformatics analysis led us to consider miR-200c-3p as a TLN1-targeting miRNA. To test this, we have generated miR-200c-3p-overexpressing and miR-200c-3p-underexpressing  cell lines, including HEK293T, HCT116, and LNCaP cells. Overexpression of miR-200c-3p resulted in a remarkable decrease in the expression of TLN1, which was associated with the suppression of integrin-mediated cell adhesion to fibronectin. In contrast, the reduction in endogenous miR-200c-3p levels led to increased expression of TLN1 and enhanced cell adhesion to fibronectin and focal adhesion plaques formation. Moreover, miR-200c-3p was found to target TLN1 by binding to its 3′-untranslated region (UTR). Taken together, our data indicate that miR-200c-3p contributes to the regulation of integrin activation and cell adhesion via the targeting of TLN1.